Pola Pertumbuhan Bibit Anggrek (Dendrodium sp.) Dalam Tahapan Aklimatisasi Pada Pengaruh Naungan dan Media Tanam - Susanti Diana; Firnawati Sakalena; Ekawati Danial; Yulhasmir Yulhasmir; Adiran Putra Yasa; Eka Rizki Meiwinda; Fitri Yetty Zairani; Nico Sebayang (Jurnal Penelitian Pertanian Terapan, 2024)
The research was conducted at the Experimental Garden of the Faculty of Agriculture, Baturaja University. Ogan Komring Olu Regency. The materials used were: Dendrobium sp orchid seedlings, charcoal, ferns, coconut fiber. The tools used were plastic/paranet, 7 cm diameter plastic pots. ruler, pot rack, treatment labels, stationery, and cameras. The study used a Randomized Block Design (RAK). The factorial treatment consisted of a combination of Shade (N), and planting media composition (M), the combination of Shade (N) consisted of 3 levels and the composition of the planting media consisted of 3 levels, the treatment was repeated three times so there were 27 combinations. Each treatment consisted of 5 plants with five sample plants. The variables observed were the percentage of growth, plant height, number of leaves, number of roots, root length, and wet weight of the plant. From the results, it was obtained that the average vegetative appearance of dendrobium orchid seedlings from the shade and planting media treatments showed more vigorous growth than without shade. The average growth of shaded seedlings was higher than without shade. Growth was higher in 50% shade. The average growth of orchid seedlings was higher in coconut fiber, fern, and rice husk charcoal (1:1:1) planting media except for leaf chlorophyll content. Correlation regression testing of the percentage of survival determined plant height by 0.55. number of leaves 0.19, dry plant weight 0.57, root length 0.005, number of roots 0.63, and leaf chlorophyll content 0.41. Based on the coefficient of determination (R2), the percentage of plant growth correlated with the number of roots, dry plant weight and plant height. The conclusion of this study is based on the plant growth pattern, the use of 50% shade and the use of coconut fiber, fern, and rice husk charcoal (1:1:1) planting media is a better treatment for the growth of Dendrobium sp. Orchids. The percentage of survival determined plant height by 0.55. number of leaves 0.19, dry plant weight 0.57, root length 0.005, number of roots 0.63, and leaf chlorophyll content 0.41. From the results of the determination coefficient (R2), it can be seen that the percentage of plant growth is correlated with the number of roots, dry weight of the plant and plant height.